2009
DOI: 10.1016/j.nurt.2009.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the NMDA Receptor Subunit NR2B for the Treatment of Neuropathic Pain

Abstract: Summary:Neuropathic pain is generally defined as a chronic pain state resulting from peripheral or central nerve injury, or both. An effective treatment for neuropathic pain is still lacking. The NMDA receptor, one type of the ionotropic glutamate receptors, is known to be important for triggering long-lasting changes in synapses. NMDA receptor-dependent synaptic plasticity plays roles not only in physiological functions such as learning and memory, but also in unwanted pathological conditions such as chronic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
121
1
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(130 citation statements)
references
References 88 publications
1
121
1
4
Order By: Relevance
“…GluN2B-selective antagonists act as negative modulators, and a small degree (ϳ10%) of receptor function remains even at saturating concentrations, which may also limit undesirable effects. GluN2B-selective antagonists have efficacy in a wide variety of preclinical models (Chizh et al, 2001;Chazot, 2004;Gogas, 2006;Mony et al, 2009;Wu and Zhuo, 2009). It is noteworthy that GluN2B antagonists do not cause behavioral disruption in preclinical species, suggesting that specifically targeting the GluN2B subunit may capture the efficacy afforded by pan-NMDA receptor inhibition and retain good tolerability.…”
Section: The Next Generation N-methyl-d-aspartate Receptor Antagonmentioning
confidence: 99%
See 1 more Smart Citation
“…GluN2B-selective antagonists act as negative modulators, and a small degree (ϳ10%) of receptor function remains even at saturating concentrations, which may also limit undesirable effects. GluN2B-selective antagonists have efficacy in a wide variety of preclinical models (Chizh et al, 2001;Chazot, 2004;Gogas, 2006;Mony et al, 2009;Wu and Zhuo, 2009). It is noteworthy that GluN2B antagonists do not cause behavioral disruption in preclinical species, suggesting that specifically targeting the GluN2B subunit may capture the efficacy afforded by pan-NMDA receptor inhibition and retain good tolerability.…”
Section: The Next Generation N-methyl-d-aspartate Receptor Antagonmentioning
confidence: 99%
“…Preclinical pharmacological (Taniguchi et al, 1997;Boyce et al, 1999;Suetake-Koga et al, 2006) and genetic (Wei et al, 2001;Tan et al, 2005) studies indicate that GluN2B subunit-containing NMDA receptors may be specifically targeted to treat neuropathic pain (Chizh et al, 2001;Wu and Zhuo, 2009). Prompted by these data, the analgesic efficacy of a single dose of CP-101,606 was tested in a small number of patients suffering from pain due to spinal cord injury and monoradiculopathy, and a clinically meaningful reduction in reported pain was observed (Sang et al, 2003).…”
Section: N-methyl-d-aspartate Antagonistsmentioning
confidence: 99%
“…These receptors are widely expressed, require binding of both glycine and glutamate for activation, and have been implicated in physiological processes such as neuronal development, synaptic plasticity, and learning and memory (Citri and Malenka, 2008;Traynelis et al, 2010). Numerous pathological conditions have also been suggested to involve NMDA receptors, including ischemic damage (Hardingham and Bading, 2010), chronic pain (Wu and Zhuo, 2009), psychosis (Coyle et al, 2003), depression (Preskorn et al, 2008), and major degenerative disorders such as Parkinson's and Alzheimer's diseases (Reisberg et al, 2003;Hallett and Standaert, 2004; see also Mony et al, 2009a;.…”
Section: Introductionmentioning
confidence: 99%
“…10,30) N-Methyl-D-aspartate (NMDA) receptor plays key roles in the transmission of pain in naïve and chronic pain status. 39) Recent studies reported that NMDA receptor is transactivated through EphB signaling initiated by interaction with presynaptic Ephrin B1. [40][41][42] When the profiling of LPAinduced and BoNT/C3 reversible genes in DRG was performed, ephrin B1 was found in 82 unique genes.…”
Section: Introductionmentioning
confidence: 99%